Fast films [IC interconnect insulation]. - Brown, A.S.
The crux of the problem is the tiny metal wires that weave the transistors on today's chips into integrated circuits. In the most advanced ICs, transistors switch up to 10 billion times a second, and their metal interconnects can barely keep up. While interconnect delay times are stretching out, transistor switching is getting faster, sending more signals down slow lines. However, the industry thinks it is zeroing in on a solution: change the propagation characteristics of those tiny on-chip transmission lines. The line's capacitance is being lowered by changing the material that insulates it from the surrounding silicon chip as well as from neighboring wire. The capacitance depends on an insulator's dielectric constant, and so researchers are developing thin films that have a lower dielectric constant, or lower k, than the silicon dioxide insulating layer used most commonly up to now.
Keywords: Capacitance; Dielectric thin films